2021
DOI: 10.1002/mrd.23461
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromatin integrity and DNA methylation in Norwegian Red bulls of contrasting fertility

Abstract: In this study, the complexity of chromatin integrity was investigated in frozen‐thawed semen samples from 37 sires with contrasting fertility, expressed as 56‐day non‐return rates (NR56). Protamine deficiency, thiols, and disulfide bonds were assessed and compared with previously published data for DNA fragmentation index (DFI) and high DNA stainability (HDS). In addition, in vitro embryo development and sperm DNA methylation were assessed using semen samples from 16 of these bulls. The percentages of DFI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…The reads were then aligned on the bovine reference genome. Unique mapping efficiency (34.3% on average) was low but consistent with previous RRBS studies in the bovine species [ 40 , 43 , 44 ]. On average, these uniquely mapped reads aligned on 3.2 million CpGs (out of 28 million CpGs in the genome), of which 60.7% on average were covered by at least 10 reads (CpGs10) and were retained for further analysis.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The reads were then aligned on the bovine reference genome. Unique mapping efficiency (34.3% on average) was low but consistent with previous RRBS studies in the bovine species [ 40 , 43 , 44 ]. On average, these uniquely mapped reads aligned on 3.2 million CpGs (out of 28 million CpGs in the genome), of which 60.7% on average were covered by at least 10 reads (CpGs10) and were retained for further analysis.…”
Section: Resultssupporting
confidence: 90%
“…Inadequate sample size has indeed been proposed as a major obstacle to replicating fertility-related DNA methylation signatures in human sperm [ 29 ]. In line with this view, the important inter-individual variability we report here makes it unlikely that the methylation differences previously reported between small numbers of bulls of contrasting fertility ( n = 3–9 per group; [ 35 40 ]) can reflect those in a larger population with less extreme differences in fertility, thus limiting modelling approaches adapted from these datasets. Only Takeda et al [ 39 ] confirmed the differential methylation between low and high fertility bulls using a wider population ( n = 50) at 10 loci and were able to construct a predictive model that has now to be assessed on an independent cohort.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, a new study suggest that sperm methylation is a possible mechanism of age-induced poor reproductive outcomes among couples undergoing infertility treatment and that it can be used to identify the possible candidate genes for mediating the effects [87]. On the other hand, sperm cells from Norwegian red bulls of inferior fertility have less compact chromatin structure, higher levels of DNA damage, and are hypermethylated compared with bulls of superior fertility [88].…”
Section: Aberrant Sperm's Dna Methylation Patternsmentioning
confidence: 99%
“…Because unsuccessful AI can result in economic losses, extended calving intervals, increased culling rates, and lower rates of genetic gain, several studies (listed below) have investigated the association between interindividual variations of the semen epigenome and fertility traits of bulls. Some studies have highlighted differences in DNA methylation patterns between groups of bulls with different fertility scores ( Kropp et al, 2017 ; Gross et al, 2020 ; Narud et al, 2021 ; Takeda et al, 2021 ). Overall, the results reported were not concordant in terms of the genes or genomic regions targeted by differential methylation and the magnitude of DNA methylation changes.…”
Section: The Epigenome Of Bull Sperm and Its Relationships With Fertilitymentioning
confidence: 99%